Issues of collaboration, representation, meaning and emotions: utilising participant-led visual diaries to capture the everyday lives of people in mid to later life. Issue 6 (1st November 2016) - Pilcher, Katy; Martin, Wendy; Williams, Veronika
Abstract: In recent years there has been an increasing use of visual methods in ageing research. There are, however, limited reflections and critical explorations of the implications of using visual methods in research with people in mid to later life. This paper examines key methodological complexities when researching the daily lives of people as they grow older and the possibilities and limitations of using participant-generated visual diaries. The paper will draw on our experiences of an empirical study, which included a sample of 62 women and men aged 50 years and over with different daily routines. Participant-led photography was drawn upon as a means to create visual diaries, followed by in-depth, photo-elicitation interviews. The paper will critically reflect on the use of visual methods for researching the daily lives of people in mid to later life, as well as suggesting some wider tensions within visual methods that warrant attention. First, we explore the extent to which photography facilitates a 'collaborative' research process; second, complexities around capturing the 'everydayness' of daily routines are explored; third, the representation and presentation of 'self' by participants within their images and interview narratives is examined; and, finally, we highlight particular emotional considerations in visualising daily life.